2023
DOI: 10.1371/journal.pone.0280776
|View full text |Cite
|
Sign up to set email alerts
|

Transient binding sites at the surface of haloalkane dehalogenase LinB as locations for fine-tuning enzymatic activity

Abstract: The haloalkane dehalogenase LinB is a well-known enzyme that contains buried active site and is used for many modelling studies. Using classical molecular dynamics simulations of enzymes and substrates, we searched for transient binding sites on the surface of the LinB protein by calculating maps of enzyme-ligand interactions that were then transformed into sparse matrices. All residues considered as functionally important for enzyme performance (e.g., tunnel entrances) were excluded from the analysis to conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Furthermore, the functional importance of this ST pathway is supported by the exploration of druggable, cryptic, and allosteric pockets, all consistently pointing to the mouth of the ST pathway as the functional site. This is further corroborated by a recent experimental study demonstrating the ability of the ST pathway mouth to bind drugs 52 . Additionally, migration analysis using CaverDock with GaMD tunnels confirmed the capacity of the transient ST to transport the substrate and product molecules efficiently at levels comparable to the auxiliary tunnel p3, which supports the auxiliary role of the ST in LinB.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, the functional importance of this ST pathway is supported by the exploration of druggable, cryptic, and allosteric pockets, all consistently pointing to the mouth of the ST pathway as the functional site. This is further corroborated by a recent experimental study demonstrating the ability of the ST pathway mouth to bind drugs 52 . Additionally, migration analysis using CaverDock with GaMD tunnels confirmed the capacity of the transient ST to transport the substrate and product molecules efficiently at levels comparable to the auxiliary tunnel p3, which supports the auxiliary role of the ST in LinB.…”
Section: Discussionsupporting
confidence: 73%
“…Their study, conducted on LinB-Wt, indicated the ability of the ST entrance pocket to bind 1-chlorohexane. Furthermore, they showed that the experimentally tested mutation of the ST entrance pocket residue A189F increased the enzyme activity by 21.4% for 1-chlorohexane and 26.2% for 1-bromocyclohexane 52 , which highlights the importance of the ST pocket and the newly discovered ST path, which connects the active site or active site pocket to the ST pocket for LinB (Figure 4). To study the opening site of the ST at the enzyme surface and its connectivity with the active site, we used cryptic and allosteric pocket detection tools such as FTMove, PASSer 2.0, and DeepSite.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The data represents mean±stdev from the three replicates. Some identified ULSs were also observed in the recent study of transient binding sites on the LinB wild-type conducted with seven halogenated compounds, including DBE molecules 63 . Out of nine sites, three could be matched to ULSs as follows: i) site 5 corresponded to ULS6, the entrance to the p3 tunnel, ii) site 9 overlayed with ULS9, the entrance to p2c tunnel, and iii) site 4 aligned to ULS8, the entrance to p2d tunnel.…”
Section: Identifying Metastable States Of Dbe Interacting With Linb86...supporting
confidence: 54%
“…Some identified ULSs were also observed in a recent study of transient binding sites on the LinB wild-type conducted with seven halogenated compounds, including DBE molecules. 72 Out of nine sites, three could be matched to ULSs as follows: (i) site 5 corresponded to ULS6, the entrance to the p3 tunnel, (ii) site 9 overlaid with ULS9, the entrance to the p2c tunnel, and (iii) site 4 aligned to ULS8, the entrance to the p2d tunnel. Such agreement suggests conservation of those interaction sites between LinB wild-type and LinB86 mutant despite the substitutions introduced into the p1 and p3 tunnels of the mutant.…”
Section: Resultsmentioning
confidence: 99%